Analisis Yuridis Kewenangan Perawat Dalam Pengobatan Bekam Pada Praktik Keperawatan Mandiri - Gegen, Gerardus; Santoso, Aris Prio Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
In providing cupping treatment, health workers must apply patient safety so that malpractice does not occur, because in this digital era everything suspected of malpractice has been widely glimpsed by justice enforcers considering the presence of complementary therapies currently still causing controversy about ethical or not when applied in nursing services. In addition, the standard operating procedures for complementary-alternative services have not been clearly described. The problem in this study is how the authority of nurses in cupping treatment in independent nursing practice, and how the legal protection of cupping treatment in independent nursing practice. This research method uses a normative juridical approach, with secondary data collection. To find out whether there is a synchronization between the applicable regulations and the practice in the field. The data obtained were analyzed qualitatively. Based on the results of the study, it was found that nurses have the authority to perform cupping treatment obtained from non-formal education as long as the nurse has competence in the field in question and this authority is also strengthened by the existence of authority in limited circumstances. Nurses who perform cupping get preventive legal protection, which is protected by state institutions through laws and regulations that apply to nursing practitioners.